Rhaetian (Late Triassic) ostracods (Crustacea, Ostracoda) from the offshore prolongation of the North Dobrogean Orogen into the Romanian Black Sea shelf - Forel, Marie-Béatrice; Grădinaru, Eugen (European Journal of Taxonomy, 2020)
The present study evaluates the significance of Triassic ostracods from the Romanian Black Sea shelf as part of a project for the understanding of the palaeoceanographical evolution of the offshore extension of the North Dobrogean Orogen. The drill core CM31, sampled from the borehole 817 Lebăda Vest drilled on the western Romanian portion of the Black Sea shelf, contains sediments of Rhaetian, Late Triassic age. The taxonomy of ostracods obtained is discussed and adds to the scientific understanding of marine ostracods during the Rhaetian stage. We document 72 species, of which seven are new: Histriabairdia pontuseuxinusensis Forel gen. et sp. nov., Bairdiacypris argonautaii Forel sp. nov., Ceratobairdia? akhilleusi Forel sp. nov., Isobythocypris atalantella Forel sp. nov., Petasobairdia amazonella Forel sp. nov., Paracypris ovidi Forel sp. nov. and Pseudomacrocypris? kerabani Forel sp. nov. Histriabairdia Forel gen. nov. is introduced to accommodate species of the Triassic–Jurassic interval previously attributed to the modern genus Anchistrocheles. These assemblages point to an outer shelf environmental with relatively normal marine oxygenation. The oldest occurrence of Pokornyopsis, found in this material, indicates that this forerunner of modern troglobitic ostracods may not have been troglobitic in the Triassic.